Xtreme kayak Sumpul - Alvarado Rivera, Oswaldo Alfredo
The creation of new and innovative tourism products in El Salvador has become a fundamental pillar for entrepreneurs in these times, because people are getting interested more in how the entrepreneurs redesign and give another perspective in business. The project is located in the department of Chalatenango in the municipality of La Palma where the Sumpul´s River and kayaking are the main sources to develop the activity. This document shows how the project take in consideration different items to assure success such as, the creation, alliances, government support, environmental responsibility, sport, marketing, logistics, values, ethic, laws and regulations. The main objective of this project is to be a new option of tourism in El Salvador that boost economy in the community, to transport the people to a different place where they can be in contact with nature, fun and traditions in an educational sense to preserve hydric resources in the county. Keywords: Entrepreneurs; tourism products; kayaking; tourism; environmental responsibility.